2020
DOI: 10.1038/s41419-020-2554-5
|View full text |Cite
|
Sign up to set email alerts
|

Cuprous oxide nanoparticles trigger reactive oxygen species-induced apoptosis through activation of erk-dependent autophagy in bladder cancer

Abstract: Cisplatin-based chemotherapy is the first-line treatment for patients with advanced bladder cancer. However, as more than 50% of patients are ineligible for cisplatin-based chemotherapy, there is an urgent need to develop new drugs. Cuprous oxide nanoparticles (CONPs), as a new nano-therapeutic agent, have been proved to be effective in many kinds of tumors. In the present study, CONPs showed dose-dependent and time-dependent inhibitory effects on various bladder cancer cell lines (T24, J82, 5637, and UMUC3) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…Several researchers have shown that the activation of the Erk/MAPK signaling pathway could promote the proliferation, invasion, and metastasis of liver cancer cells [56][57][58]. Furthermore, Erk/MAPK signaling pathway may be a vital pathway of autophagy in cancer [59][60][61]. In the present study, we found that p-Erk expression changed with PNO1 expression.…”
Section: Discussionsupporting
confidence: 57%
“…Several researchers have shown that the activation of the Erk/MAPK signaling pathway could promote the proliferation, invasion, and metastasis of liver cancer cells [56][57][58]. Furthermore, Erk/MAPK signaling pathway may be a vital pathway of autophagy in cancer [59][60][61]. In the present study, we found that p-Erk expression changed with PNO1 expression.…”
Section: Discussionsupporting
confidence: 57%
“…Several researchers have shown that the activation of the Erk/MAPK signaling pathway could promote the proliferation, invasion, and metastasis of liver cancer cells 56 58 . Furthermore, Erk/MAPK signaling pathway may be a vital pathway of autophagy in cancer 59 61 . In the present study, we found that p-Erk expression changed with PNO1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Xiong et al. 80 showed that cuprous oxide nanoparticles (CONPs) activated ERK-mediated autophagy, which triggered ROS-induced apoptosis in orthotopic xenografts and subcutaneous nude mouse bladder cancer models. Wang et al .…”
Section: Cell Death Effects Of Autophagy On Bladder Cancer Cellsmentioning
confidence: 99%